Compensation of Temperature Effects in Long-Term Monitoring of a Highway Bridge located in the Austrian Alps. (2017) - Furtmüller, Thomas; Adam, Christoph
Abstract: This contribution addresses the compensation of temperature effects on a natural frequency of a highway bridge located in the Austrian Alps with seasonal ambient temperature fluctuation above and below freezing. This frequency identified from the ambient acceleration response recorded in a five-year monitoring campaign shows a pronounced temperature dependency. Two different methods are proposed and effectively applied to compensate this undesired temperature effect. In the first approach a direct correlation between natural frequency and ambient temperature is established, whereas the more sophisticated approach is based on a dynamic time-series model of Box-Jenkins type.